PENGARUH CAR DAN BOPO TERHADAP ROA (Studi Kasus Pada Bank Umum Syariah Tahun 2015-2016) - Rusdiana, Melati (COMPETITIVE, 2023)
The purpose of this study is to determine whether the dependent variable in this study can be influenced by the independent variable. The population in this study were 14 Islamic Commercial Banks with the sampling technique used was purposive sampling. Obtained a sample of 10 Islamic Commercial Banks registered with the OJK. In this study, multiple regression was used to test the hypothesis. Based on the results of the simultaneous test, it is known that ROA can be affected by CAR and BOPO together. Based on the partial test, ROA not can be affected by CAR and ROA can be influenced by BOPO